2019
DOI: 10.1037/dev0000654
|View full text |Cite
|
Sign up to set email alerts
|

Getting help for others: An examination of indirect helping in young children.

Abstract: When young children recruit others to help a person in need, media reports often treat it as a remarkable event. Yet it is unclear how commonly children perform this type of prosocial behavior and what forms of social understanding, cognitive abilities, and motivational factors promote or discourage it. In this study, 48 3-to 4-year-old children could choose between two actors to retrieve an out-of-reach object for a third person; during this event, one actor was physically unable to provide help. Nearly all o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Behavioral inhibition (BI), a temperamental trait characterized by high negative affect and withdrawal behaviors to novel and challenging situations in infancy and toddlerhood, has been generally considered a primary precursor of low social competence (Fox, Henderson, Marshall, Nichols, & Ghera, 2005). Children who are highly inhibited are more likely to display social withdrawal and reticence during peer interactions (Pérez-Edgar et al, 2011;Rubin, Burgess, & Hastings, 2002), present less cooperative and prosocial behavior (Karasewich, Kuhlmeier, Beier, & Dunfield, 2018;Laible et al, 2017;Stanhope, Bell, & Parker-Cohen, 1987), and experience increased risk for internalizing behaviors and anxiety (Clauss & Blackford, 2012;Putnam & Stifter, 2005;Schwartz, Snidman, & Kagan, 1999;Williams et al, 2009). In addition, research has demonstrated that higher BI is linked to lower empathy, which is an important social competence that supports the understanding of others' emotional and mental states and aids in navigating social behaviors (Eisenberg, Spinrad, Taylor, & Liew, 2019;Liew et al, 2011;Young, Fox, & Zahn-Waxler, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral inhibition (BI), a temperamental trait characterized by high negative affect and withdrawal behaviors to novel and challenging situations in infancy and toddlerhood, has been generally considered a primary precursor of low social competence (Fox, Henderson, Marshall, Nichols, & Ghera, 2005). Children who are highly inhibited are more likely to display social withdrawal and reticence during peer interactions (Pérez-Edgar et al, 2011;Rubin, Burgess, & Hastings, 2002), present less cooperative and prosocial behavior (Karasewich, Kuhlmeier, Beier, & Dunfield, 2018;Laible et al, 2017;Stanhope, Bell, & Parker-Cohen, 1987), and experience increased risk for internalizing behaviors and anxiety (Clauss & Blackford, 2012;Putnam & Stifter, 2005;Schwartz, Snidman, & Kagan, 1999;Williams et al, 2009). In addition, research has demonstrated that higher BI is linked to lower empathy, which is an important social competence that supports the understanding of others' emotional and mental states and aids in navigating social behaviors (Eisenberg, Spinrad, Taylor, & Liew, 2019;Liew et al, 2011;Young, Fox, & Zahn-Waxler, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have shown that displays of caring and concern emerge as early as 8-10 months and gradually increase across the second year of life (e.g., Roth-Hanania, Davidov, & Zahn-Waxler, 2011), these studies rarely differentiate among different forms of prosocial behavior. For example, the seminal work by Zahn-Waxler and colleagues included different codes for instrumental, emotional, and indirect helping (Roth-Hanania et al, 2011;Zahn-Waxler, Radke-Yarrow, & King, 1979;Zahn-Waxler, Radke-Yarrow, et al, 1992;Zahn-Waxler, Robinson, & Emde, 1992), and similar distinctions have also been noted by other researchers (e.g., Dunfield et al, 2011;Fabes, Eisenberg, Karbon, Troyer, & Switzer, 1994;Karasewich, Kuhlmeier, Beier, & Dunfield, 2019). However, despite distinguishing between functionally distinct forms of prosocial behavior in their coding, prior research often collapses these behaviors into a more general "helping" behavior, which may obscure important distinctions in how infants help and in what contexts.…”
Section: Distinct Prosocial Response Strategiesmentioning
confidence: 89%
“…Furthermore, the few studies that have examined distinct forms of infant prosocial behavior have often done so by tailoring a specific context to be addressed (Dunfield, 2014;Dunfield et al, 2011;Karasewich et al, 2019;Svetlova et al, 2010). For example, infant helping when the experimenter has an instrumental need is deemed instrumental helping.…”
Section: Distinct Prosocial Response Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings point to the role of socialization in the early emergence of helping (for reviews see Brownell et al, 2016;Dahl, 2018) and suggest that by the end of the second year, helping behavior is an established routine. When they are prevented from helping themselves, 2.5-year-old toddlers (but not 1.5-to 2-year-olds) systematically involve their own caregivers to help a needy other (Paulus et al, 2017; see also Karasevich, Kuhlmeier, Beier, & Dunfield, 2018), indicating a motivation to see others being helped. Similarly, by 2 years toddlers show signs of proactive helping, that is, help spontaneously by putting an object back on a table without being requested to do so (Warneken, 2013).…”
Section: From Early Social Interaction To Other-oriented Behaviormentioning
confidence: 99%